The impact of attention deficit hyperactivity disorder on medical students’ academic performance and well-being: a letter to the editor - Muhammad Ahmed Zahoor,; Sahar Imtiaz,; Jillani, Sheikh Abdul Qadir (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Attention Deficit Hyperactivity Disorder (ADHD) is a common neuropsychiatric condition characterized by developmentally inappropriate inattention and/or hyperactivity-impulsivity. ¹ Though this has traditionally been considered a childhood disorder, it is now being increasingly understood that ADHD symptoms may persist into adulthood. The estimated prevalence of clinician assessed ADHD in the adult population is estimated to lie between 5-10%. ² The disorder can cause significant functional impairment and academic underachievement, especially in a university environment. Transitioning into medical school brings a curriculum that is intense and very demanding, a challenge taken to a much higher level by students with ADHD. It changes the dimensions of self-regulation, time management, and organization. Some of the most essential skills for medical school students with ADHD are long lectures and clinical hour focus, time management concerning multiple deadlines, and juggling multifaceted coursework and clinical tasks. Most of the time, these academic and practical issues typically result in incomplete assignments and general underperformance in academics. Research consistently shows that such students generally have lower GPAs, high dropout rates, and longer times to attain medical degrees compared to their non-ADHD peers. ³ The ongoing academic challenges faced by these students can also impact their mental health, where they experience high levels of stress, anxiety, and depression.4 Furthermore, the academic difficulties that those with ADHD face, weaken their social interactions, leading to feelings of isolation and, eventually, social withdrawal. This compounded problem highlights the need for comprehensively designed support systems with individual differences for medical students with ADHD. Comprehensive care should be the approach when treating medical students diagnosed with ADHD. Some individualised academic accommodations that may help alleviate some academic stress include extended time on exams, note-taking services, and flexible deadlines for assignments. Also, such students should have access to mental health resources such as counselling and ADHD coaching. Professional development programs for faculty in medical schools can also help equip faculty with strategies to handle students with ADHD within the classroom and clinical settings. By applying the following methods, medical schools could allow students with ADHD to reach their maximum potential in both academic and professional life, thus contributing to improving their quality of life.